Problematika Perusahaan Grup: Bentuk dan Potensi Praktik Monopoli dan Persaingan Usaha Tidak Sehat - Dandi Jayusman; Reni Budi Setianingrum (Universitas Muhammadiyah Yogyakarta, 2023)
The development of group companies today is an implication of the globalization era which makes business competition more open and free and at the same time can plunge business actors into monopoly practices. The aim of this research is to analyze the problems of group companies in the Indonesian legal system and to analyze forms of monopolistic practices and unfair business competition through the business strategy of group companies (groups). While the method used is the normative legal research method using statutory approaches, case approaches, and conceptual approaches. The results of this study indicate that the problems of group companies in Indonesia occur due to the regulation based on the 2007 UUPT using a single company approach, which legally recognizes that the parent company and subsidiaries in group companies are independent. The forms of monopolistic practices that are likely to be carried out by group companies are cross-share ownership, discriminatory practices and price fixing through multiple positions. This is an implication of the parent company's controlling power and full dominance in determining the policies and business activities of its subsidiaries.